Uncommon Odontogenic Orocutaneous Fistula of the Jaw Treated with Platelet-Rich Fibrin - Kani Bilginaylar (Case Reports in Dentistry)
Orocutaneous fistula (OCF) of dental origin is a relatively rare condition and continues to be a challenging diagnosis. Misdiagnosis of OCF usually leads to unnecessary and noneffective treatment. A 21-year-old male referred with a complaint of a lesion on the chin which was misdiagnosed as a carbuncle (lesion of nonodontogenic origin) by a physician. After radiological examination, there was a lesion around the apical region of right central incisor. These findings indicated a sinus tract associated with dental origin. After root canal treatment, apical surgery was performed and platelet-rich fibrin (PRF) was administered to the cavity of the lesion as a gel form to improve healing and also used as a membrane form to cut off the relation between infected area and the skin. All procedures were performed intraorally; no extraoral intervention was performed. Three months later, clinical and radiological examination showed total healing without scar formation. The key to successful treatment of OCF is accurate diagnosis. Additionally, the use of PRF after surgical interventions is an effective and innovative therapy to improve healing.